Assessing the developmental trajectory of mouse models of neurodevelopmental disorders: Social and communication deficits in mice with Neurexin 1α deletion. (30th December 2019) - Armstrong, Emily C.; Caruso, Angela; Servadio, Michela; Andreae, Laura C.; Trezza, Viviana; Scattoni, Maria L.; Fernandes, Cathy
Abstract: Neurexin 1α mutations are strongly associated with neurodevelopmental disorders such as autism spectrum disorders and schizophrenia in humans. Studies using the Neurexin 1α knock‐out mouse have showed behavioral abnormalities of relevance to these disorders and baseline deficits in excitatory synaptic function have been described. However, little is known about the effect of Neurexin 1α deletion on behavior during development. This study examined the effects of Neurexin 1α deletion on behavior across a range of developmental time points to determine whether potential abnormalities follow a developmental trajectory. Pups lacking Neurexin 1α emitted a reduced number of ultrasonic vocalizations early in development combined with a restricted repertoire of calls indicative of a loss in complexity in vocal production and showed delays in reaching certain developmental milestones. Behavioral testing showed that juvenile and adult male Neurexin 1α knock‐out mice exhibited social deficits and increased levels of aggression, confirming previous findings. No increases in repetitive behaviors or deficits in motor learning or olfaction were seen. In conclusion, this research showed that Neurexin 1α deletion does result in social and communication deficits that follow a developmental trajectory. These are the first experimental data that associate a deletion of Neurexin 1α with alterations in behaviors relevant to autism spectrum disorder across development and highlight the importance of assessing the developmental trajectory in mouse models of neurodevelopmental disorders. Abstract : We report the first experimental data that associate a deletion of Neurexin 1α with alterations in behaviors relevant to autism spectrum disorder across development and highlight the importance of assessing the developmental trajectory in mouse models of neurodevelopmental disorders. Mice lacking Neurexin 1α emit a reduced number of ultrasonic vocalizations early in development combined with a restricted repertoire of calls indicative of a loss in complexity in vocal production (Figure 1. Altered of sonographic structure of ultrasonic vocalizations in Nrxn1α knockout pups compared with wildtype pups in response to social separation).